Changes in kinematics induced by fatigue during 200M freestyle swimming - Sumi, N.; Matsuda, Y.; Akashi, K.; Tagawa, T.; Nishiwaki, T. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Competitive swimmers strive to obtain good postures and motions in water for performance enhancement because they could be a determining factor for competitive races. It is clear that fatigue affects swimming kinematics fairly but the effect has not been quantitatively evaluated yet. The finding of biomechanical change would be helpful for elucidating the mechanism of swimming slower. The purpose of this study is to quantitatively investigate changes in kinematics during 200M freestyle swimming. 14 female freestyle or individual medley swimmers joined the experiment where they swam 200M by the crawl with their best efforts. They wore their usual practice swimsuits with reflective markers. The swimming movements were measured with a 3 dimensional motion capture system at 50M intervals. Blood lactate was also measured before and after the task of 200M swimming to monitor their fatigue levels. It was shown that their swimming speed decreased clearly with the swimming distance and the blood lactate levels also increased after the task. Biomechanical analysis indicated that rotation of trunk and pelvis increased while the position of the pelvis went down and kept low, seemingly causing the drag force in water higher.